2016
DOI: 10.1001/jamadermatol.2015.4190
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Confirmatory Testing Before Treatment of Onychomycosis

Abstract: IMPORTANCE Onychomycosis is the most common disease of the nail in adults. International guidelines urge health care professionals to perform confirmatory diagnostic testing before initiating systemic therapy. This approach was determined to be cost-effective in studies from the late 1990s but has not been evaluated more recently. The effect of testing on the costs of efinaconazole, 10%, topical solution treatment is unknown.OBJECTIVE To evaluate the cost and potential harm associated with 3 approaches to onyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 12 publications
1
48
0
1
Order By: Relevance
“…Despite the cost savings of performing confirmatory testing prior to treatment, family practitioners almost never perform mycological tests (46.6%) while dermatologists almost always conduct a mycological test (63.5%) . This result is compounded by the fact that clinicians (excluding dermatologists and podiatrists) have a lower positive predictive value (66%) in diagnosing onychomycosis as compared to dermatologists (75%) . Thus, incorporating mycological testing into the definition of cure is cost effective and an aid to those not well versed in onychomycosis …”
Section: Discussionmentioning
confidence: 99%
“…Despite the cost savings of performing confirmatory testing prior to treatment, family practitioners almost never perform mycological tests (46.6%) while dermatologists almost always conduct a mycological test (63.5%) . This result is compounded by the fact that clinicians (excluding dermatologists and podiatrists) have a lower positive predictive value (66%) in diagnosing onychomycosis as compared to dermatologists (75%) . Thus, incorporating mycological testing into the definition of cure is cost effective and an aid to those not well versed in onychomycosis …”
Section: Discussionmentioning
confidence: 99%
“…6,8 Confirmatory diagnosis is made by fungal stain (or KOH preparation) and culture of scrapings of debris following alcohol swabbing and nail clipping as described by Gupta et al 33 However, a recent analysis indicated that empiric treatment of onychomycosis with terbinafine is more cost-effective than confirmatory testing with fungal periodic acidSchiff stain or KOH prep. 34 The opposite was true for treatment with 10% topical efinaconazole. 34 Majocchi's Granuloma: Majocchi's granuloma occurs when dermatophytes like T. rubrum --or, rarely, nondermatophytes such as Aspergillus sp.…”
Section: Pathophysiologymentioning
confidence: 99%
“…34 The opposite was true for treatment with 10% topical efinaconazole. 34 Majocchi's Granuloma: Majocchi's granuloma occurs when dermatophytes like T. rubrum --or, rarely, nondermatophytes such as Aspergillus sp. --invade the dermis and subcutaneous tissue, usually via disrupted hair follicles ( Figure 11).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Laser therapy is currently not covered by health insurance plans and can cost from $400 to $1 #bib200 US per session . Comparatively the cost of terbinafine, an approved onychomycosis treatment, is $10 US for a 12 week course . Another major difference between oral, topical and laser treatments is treatment duration.…”
Section: Discussionmentioning
confidence: 99%